Hegemony, Pan-Americanism, and national security: the meaning and application of the Monroe Doctrine in the early twentieth century - Bryne, Alex (2018)
This thesis traces the history of the Monroe Doctrine during the early twentieth century and examines the ways in which its meaning was reinterpreted between the Spanish-American War of 1898 and its centennial anniversary in 1923. It argues that United States foreign policy elites engaged in a protracted and unprecedented debate over the doctrine’s meaning and application for a quarter-century, transforming it into a national security framework that justified new directions in United States foreign relations, whilst simultaneously facilitating debate and contestation. As politicians, diplomats, academics, international lawyers, and high-ranking military figures scrutinised the value and importance of the doctrine, its meaning fractured into two overarching reinterpretations that were each aligned to antithetical core values of United States national security, namely regional hegemony in the Western Hemisphere and inter-American cooperation. Both ideals were deemed essential to the existence and security of the United States, and the Monroe Doctrine was reinterpreted to maintain these core values that it was perceived to embody. The expansion of the United States Empire through informal, economic, and colonial imperialism during the early twentieth century clashed with the simultaneous growth of the Pan-American movement, and the doctrine’s capricious meaning reflected the discord that permeated national perceptions of the United States’ role in the world. Drawing upon a collection of archival material and published primary sources, including governmental documentation, personal papers, congressional debates, academic publications and conference papers, and literary-political magazines and newspapers, this thesis addresses the complicated relationship between notions of hegemony and cooperation in the conduct and formation of United States foreign relations. Through analysing the Monroe Doctrine debate of the early twentieth century, this study provides a nuanced account of the doctrine’s evolution throughout major events, such as the annexation of the Philippines, the construction of the Panama Canal, the Mexican Revolution, the First World War, and the treaty fight; positions Latin America at the heart of United States national security; and offers a critical insight in the identification of United States core values.